THE PHENOMENON OF "CLICK" AND THE PRINCIPLE OF GOOD FAITH IN ONLINE BUYING AND SELLING: A PHILOSOPHICAL PERSPECTIVE ON BUSINESS LAW - Wahyu Prawesthi; Joice Soraya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The development of information and communication technology has driven the growth of the increasingly popular phenomenon of online buying and selling, but it has also brought legal issues related to the principle of good faith in such transactions. In the context of online buying and selling, the action of "clicking" as an expression of intent to enter into a sales agreement has legal implications, but it is not yet clear whether it truly reflects free will and good faith considering the virtual nature of transactions which are vulnerable to issues such as lack of clarity in information or fraud. This research aims to examine the phenomenon of "clicking" in online buying and selling transactions from the perspective of the philosophy of business law and its relation to the principle of good faith in contract law, as well as to analyze the legal developments and regulations in Indonesia in accommodating this phenomenon along with the challenges faced in its implementation. This research uses a normative legal research method. A conceptual approach is used to understand the concepts and principles of law related to the phenomenon of "clicking" and the principle of good faith in online buying and selling in depth from the perspective of the philosophy of business law, by collecting data through literature review and analyzing the data qualitatively. The research findings show that the review of the philosophy of business law emphasizes that the action of "clicking" in online buying and selling transactions should be regarded as a manifestation of free will and good faith if based on complete and transparent information, and there is no imbalance in bargaining positions between businesses and consumers. Efforts to enhance transparency, strengthen consumer protection, and enforce the law rigorously are needed to create a fair and dignified online buying and selling ecosystem. Meanwhile, regulatory developments in Indonesia such as the ITE Law and the PMSE Regulation have not specifically accommodated the phenomenon of "clicking" and the principle of good faith, with the main challenges being the dynamic nature of digital technology, gaps with conventional legal principles, and the need to ensure a balance of interests and enhance public education on safe online buying and selling transactions.